Discursive constructions of new wine companies in the province of San Juan, Argentina (2024)
During the 1990s in the province of San Juan-Argentina, a series of agriculturalprojects were promoted that produced a territorial reorganization of the wine frontier. Thesetransformations, promoted by Law 22.021, took place in a context of criticism of the deferralpolicy. The objective of this research was to analyse the new discursive constructions emergingfrom this policy, addressing the trajectory of regional identity and its tensions. Based on aflexible research design that combined documentary analysis techniques, statistical dataanalysis and in-depth interviews, the discursive strategies adopted by the companies thatbenefited from deferrals were investigated. It is concluded that this new stage caused tensionsin the traditional winegrowing identity. The arrival of new companies and the diversificationtowards olive growing, driven by these tax incentives, contributed to the transformation of SanJuan’s centuries-old identity narrative. The traditional agrarian valuations on which viticulturehad rested were displaced by a less cohesive construction. That is to say, more particularized,company by company, marking an identity differentiation with the previous period. At thesame time, there was a process of material and symbolic reappropriation in which traditionalimages were merged with new ones.